Invention through bricolage: epistemic engineering in scientific communities (RT. A Journal on Research Policy and Evaluation, 2018)
It is widely recognised that knowledge accumulation is an important aspect of scientific communities. In this essay, drawing on a range of material from theoretical biology and behavioural science, I discuss a particular aspect of the intergenerational nature of human communities – “virtual collaboration” (Tomasello 1999) – and how it can lead to epistemic progress without any explicit intentional creativity (Henrich 2016). My aim in this paper is to make this work relevant to theorists working on the social structures of science so that these processes can be utilised and optimised in scientific communities.
Keywords: Social Structure of Scientific Communities; Virtual collaboration; Interdisciplinarity; Cognitive diversity